PENGARUH PENAMBAHAN LIMBAH GIPSUM TERHADAP KUAT TEKAN BETON - Rafki Imani; Widiawati Purba; Rainaldi S Nainggolan (Construction and Material Journal, 2020)
Concrete is composed of three main constituent materials, namely cement, aggregate and water. The development of concrete technology in the trial of adding a mixture of materials continues to be done to achieve the desired strength and quality. In this experiment, the addition of gypsum waste was used as a concrete mixture to determine its effect on the compressive strength of concrete. The variation in the percentage of the addition of gypsum waste is 5%, 10%, and 15% with the age of treatment observed at 14 days and 28 days. The results showed that the normal compressive strength value at 14 days was 186.87 kg/cm2, while with the addition of gypsum waste mixture the concrete compressive strength at 5%, 10% and 15% were obtained 178.45 kg respectively /cm2, 101, 01 kg/cm2, 70.71 kg/cm2. Meanwhile the compressive strength value of normal concrete at 28 days is 164.44 kg/cm2, and the compressive strength value of concrete after mixed with gypsum waste at 28 days is obtained 157.04 kg/cm2, 88.89 kg/cm2, 62.22 kg/cm2. Based on the results it can be concluded that the addition of gypsum waste as a concrete mixture material can reduce the compressive strength values of normal concrete. Keywords : Concrete, Compressive Strength, and Gypsum Waste.